2018
DOI: 10.1002/14651858.cd000323.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Swallowing therapy for dysphagia in acute and subacute stroke

Abstract: Background Dysphagia (swallowing problems), which is common a er stroke, is associated with increased risk of death or dependency, occurrence of pneumonia, poor quality of life, and longer hospital stay. Treatments provided to improve dysphagia are aimed at accelerating recovery of swallowing function and reducing these risks. This is an update of the review first published in 1999 and updated in 2012. Objectives To assess the e ects of swallowing therapy on death or dependency among stroke survivors with dysp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
156
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 169 publications
(180 citation statements)
references
References 157 publications
1
156
0
5
Order By: Relevance
“…Moderate-quality evidence suggested that swallowing interventions reduced hospital length of stay but that these interventions did not reduce case fatality rate or the combined outcome of death or disability. 44 Higher-quality evidence to support the positive impact of rehabilitative interventions for dysphagia in older adults with a variety of etiologies is desperately needed.…”
Section: Rehabilitative Interventionsmentioning
confidence: 99%
“…Moderate-quality evidence suggested that swallowing interventions reduced hospital length of stay but that these interventions did not reduce case fatality rate or the combined outcome of death or disability. 44 Higher-quality evidence to support the positive impact of rehabilitative interventions for dysphagia in older adults with a variety of etiologies is desperately needed.…”
Section: Rehabilitative Interventionsmentioning
confidence: 99%
“…Subsequently nine studies were excluded, and the reasons for exclusion were as follows: one SR included observational studies, two articles were conference abstracts, one SR we were unable to get the full text, four studies were not SRs, and one article was a duplicate. Finally, 31 studies were included in our study [8][9][10]. The study flow chart is shown in Figure 1.…”
Section: Selection Of the Systematic Reviews And Meta Analysesmentioning
confidence: 99%
“…A total of 31 studies were published between 2006 and 2019 [8][9][10], nine SRs [8][9][10][36][37][38][39][40][41] were published in English-language journals, and the remaining 22 were in the Chinese-language. Four of the 31 SRs were Cochrane reviews [8][9][10]41], 21 were journal articles [14][15][16][17][18][19][20][21][22][23][24][25][26][27]29,30,[36][37][38][39][40], one was a conference paper [28] and five were theses (three Masters and two PhDs degrees) [31][32][33][34][35]. The first authors of 29 SRs [8, were from China, including one [39] from Hong Kong, and the first author of the other two SRs were from UK [10] and Sri Lanka [9] but with the same corresponding author from UK.…”
Section: Characteristics Of Systematic Reviewsmentioning
confidence: 99%
See 2 more Smart Citations